Neonatal Nurse Practitioner Use of Ultrasonography to Verify Umbilical Venous Catheter Placement in the Neonatal Intensive Care Unit. (August 2020) - Mele, Robert; Panesar, Laurie E.; Heyden, Marybeth; Sridhar, Shanthy; Brandon, Debra
Abstract : Background: Literature dating back to 1982 supports the use of ultrasound to confirm UVC position as a more reliable method compared to x-ray. The use of ultrasound to confirm UVC position remains infrequent in the NICU. Purpose: To determine the feasibility of training an NNP in the acquisition and interpretation of a parasternal short-axis (PSAX) image of the heart to confirm UVC position. Methods: A retrospective review of 48 charts evaluated descriptive data using standard technique of an x-ray to confirm UVC placement. An NNP was trained to acquire and interpret a parasternal short-axis (PSAX) cardiac view by a pediatric cardiologist. The NNP independently and prospectively evaluated 21 neonates and determined whether the UVC was in satisfactory or unsatisfactory position. The same image was blindly over-read by the pediatric cardiologist. Agreement between the NNP and pediatric cardiologist interpretations as well as the pediatric cardiologist and radiologist interpretations was evaluated using the κ-test. Results: Initial pediatric cardiology interpretation of UVC position showed the UVC to be malpositioned in 66% of neonates (n = 14). NNP and pediatric cardiology interpretations in UVC position had 86% agreement (κ-0.667). Pediatric cardiology (ultrasound) and radiology interpretations (x-ray) in UVC position had 86% agreement (κ-0.69). Implications for Practice: It is feasible to train NNPs to perform and accurately interpret a single PSAX ultrasound image to determine satisfactory UVC position. Implications for Research: Increasing the use of ultrasound to determine satisfactory position of UVCs in the NICU can reduce unnecessary exposure to ionizing radiation in neonates.